Assessment of Nigerian mango (Mangifera indica) seed-kernel as a substitute for maize in finishing broiler diets - ODUNSI, A A.; FARINU, G O (The Indian Journal of Animal Sciences, 2013)
Mango seed-kernel (MSK) contains 5.59% crude protein, 2.13% ether extract, 2.34% ash, 5.32% crude fibre, 78.62% nitrogen free extracts and estimated 3.17 kcal/g ME. five diets in which MSK replaced 0, 10, 20,30 and 40.% levels of dietary maize were fed ad lib. to finishing broilers (2g-63 days). The effects on performance, nutrient rentrion, carcass yield and composition were investigated. Inceasing substitution of maize above 30% redued (P<0.05) weight gain and feed intake relative to control. Replacement at 20% level by MSK resulted 10 better (P<0.05) gain than control. gain/food and morality showed no significant differences (P<0.05) among dietary treatments. Dry matter and ash retention were unaffected but protein and fat retention values decreased (P<0.05) as dietary MSK increased. Carcass dressing percentage depressed (P<0.05) at higher levels with birds on MSK diets. Broiler cut-up parts, liver and muscle protein, fat, ash and dry matter were not negatively influenced even at 40% level of replacement.